STUDI DESAIN PERPUSTAKAAN INKLUSI BERBASIS ICT BAGI PENYANDANG DISABILITAS DI SEKOLAH - Hafid, Afdhil; Setia Utami, Iga (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
This study looks at the issue of e-inclusion in the field of school education. It aims to explain the potential that Information and Communication Technology (ICT) offers to avoid any form of discrimination among students. The basic idea underlying this paper is that the process of school inclusion can be fostered through new technological tools only if, in parallel, educational approaches, methods and strategies are easily revised and improved. Taking the point of view of both educational tools and methods, this paper discusses the key issues of the “accessibility” of educational tools and the “new competencies” required by teachers. To build truly inclusive classrooms on the one hand, key educational tools (including ICT-based ones) need to be barrier-free and fully accessible to all students, and, on the other hand, for teachers to have them. competence to carefully select e-tools and plan/utilize them properly.